Costs and benefits of dual apprenticeship : lessons from the Swiss system - Hanhart, Siegfried [Verfasser]; Bossio, Sandra [Verfasser] (My University, 1998)
"Though little known, Switzerland's apprenticeship system has proven its effectiveness for nearly a century. On completing their compulsory schooling, nearly two-thirds of the country's young people undertake such training with alternating periods of enterprise-based trainging and attendance at a vocational school. The system's many advantages include the involvement of enterprises, easier labour market entry and trilateral funding. Drawing on the findings of a survey of a representative sample of enterprises, the authors explain how the system works and evaluate its costs to enterprises. They examine the enterprises' incentives and disincentives to train apprentices and look at the system's future prospects." (author's abstract, IAB-Doku) ((en)) Darstellung des schweizerischen Systems der dualen Berufsausbildung und Evaluation des Nutzens und der Kosten für die Unternehmen. (IAB)
Keywords: S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; S 1.3.1 Ausbildung im Dualen System; I 2.2.1 Westeuropa; Berufsausbildung; Kosten-Nutzen-Analyse; Duales System; Quantitative Angaben; Schweiz